(untitled) (Indonesian Journal of Agrarian Law, 2026)
The problem of abandoned land reflects inconsistency between land utilization and the principle of the social function of land under Indonesian agrarian law. One indication of abandoned land is the existence of abandoned buildings, demonstrating that land is not cultivated, utilized, used, or maintained according to the purpose for which the land right was granted. This study analyzes the responsibilities of land rights holders and the authority of local governments in controlling abandoned land associated with abandoned buildings under Government Regulation Number 48 of 2025, using the former PT Telkom building in Kudus Regency as a case study. The research employs an empirical juridical method with statutory and case study approaches. Data were collected through library research, field observations, and interviews and analyzed qualitatively. The findings indicate that the land occupied by the former PT Telkom building shows signs of abandonment because it has not been utilized or maintained in accordance with the purpose of the granted land right, as reflected by the prolonged existence of abandoned buildings. This condition demonstrates the inadequate implementation of land rights holders’ responsibilities and contradicts the principle of the social function of land. Furthermore, local government efforts remain ineffective due to regulatory ambiguities, limited authority over certain assets, inadequate land administration data, and weak inter-agency coordination. Therefore, strengthening regulations, improving institutional coordination, and optimizing supervision of land utilization are essential to ensure effective control of abandoned land and the realization of its social function.